Ethnobotanical study of medicinal plants for postpartum remedies by the Dayak Bakumpai Tribe in Central Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hujjatusnaini N, Fitri DRK, Nirmalasari R, Mila, Amin AM. 2025. Ethnobotanical study of medicinal plants for postpartum remedies by the Dayak Bakumpai Tribe in Central Kalimantan, Indonesia. Biodiversitas 26: 2946-2956. Numerous studies on the ethnobotany of the Dayak Bakumpai Tribe in Central Kalimantan have been conducted, yet those focused on medicinal plants with particular remedial purpose is limited. This research aims to investigate the ethnobotanical knowledge of Dayak Bakumpai for postpartum remedies. Field surveys were conducted in seven districts: Seruyan, Katingan, East Barito, North Barito, South Barito, East Kotawaringin, and West Kotawaringin, involving 250 respondents selected using snowball method. The research identified 47 plant species from 40 genera, and 27 families used as remedies to treat postpartum ailments. Leaves are the most commonly used plant part with 25 species (67.57%), followed by entire plant with 10 species (21.28%). The modes of application include in the form of liquid preparations (27 species), solid preparations (12 species), topical preparations (4 species), and hydrotherapy preparations (18 species). Plant with the highest Cultural Significance Index values are Ageratum conyzoides, Curcuma domestica, and Ficus deltoidea. Preserving ethnobotanical knowledge of medicinal plants for postpartum treatment is a key aspect of maintaining the local wisdom and culture of the Dayak Bakumpai Tribe.
Keywords: Bakumpai Tribe, ethnobotanical, herbal remedies, postpartum